THE FATE OF FIRDAUSI IS IN HEINRICH HEINE’S INTERPRETATION (Scientific journal of the Fergana State University, 2023)
In this article the polemic aspects of interpretation of the fate of Firdausi in the work of the great poet H. Heine are analyzed.